Effects of childhood and adolescence physical activity patterns on psychosis risk—a general population cohort study - Elina Sormunen (Nature Portfolio, 2017)
Risk of disease: keeping kids active Researchers in Finland show that low physical activity in childhood and early adolescence increases the risk of developing schizophrenia. Jarmo Hietala at the University of Turku and colleagues assessed data collected between 1980 and 1986 from an ongoing population study of the physical activity of 3596 participants before and after puberty. By linking these data to hospital records they found that physical activity was lower among those who later developed non-affective psychosis, particularly schizophrenia. Further, when adjusting for other known psychosis risk factors, the effect of physical inactivity remains significant. There are likely to be multiple causes for this physical inactivity, including delayed motor development before the onset of psychosis. Although the mechanism through which exercise can lower the risk of disease is unclear, there is evidence that physical activity can trigger structural and functional brain changes. These findings support including exercise and physical activity in psychosis prevention and early intervention programs.